1968
DOI: 10.1037/h0025501
|View full text |Cite
|
Sign up to set email alerts
|

Systematic desensitization as a counterconditioning process.

Abstract: Systematic desensitization, demonstrated in both clinical and experimental studies to reduce avoidance behavior, entails the contiguous pairing of aversive imaginal stimuli with anxiety-competing relaxation. If, as is widely assumed, the efficacy of the procedure derives from a genuine counterconditioning process, a disruption of the pairing between graded aversive stimuli and relaxation should render the technique ineffective in modifying avoidance behavior. This hypothesis was strongly confirmed: significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
127
4
5

Year Published

1971
1971
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(148 citation statements)
references
References 30 publications
11
127
4
5
Order By: Relevance
“…According to this strategy, one (control) group of fearful experimental participants is exposed to a theoretically ninert placebo "treatment," and any dependent-variable improvements resulting from the inert placebo are subtracted from global measures of treatment effects in order to yield pure or net measures of the effects from explicit behavioral procedures (cf. Borkovec, 1972;Davison, 1968;Marcia et al, 1969;McGlynn et al, t971;Paul, 1966). While Borkovec et al quite satisfactorily showed a subset of their measures of shyness to be unresponsive to simple, preassessment, experimental-demand instructions, they did not show these measures of shyness to be unresponsive to any of the elaborate, multisession placebo treatments that fear-therapy researchers might actually employ.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…According to this strategy, one (control) group of fearful experimental participants is exposed to a theoretically ninert placebo "treatment," and any dependent-variable improvements resulting from the inert placebo are subtracted from global measures of treatment effects in order to yield pure or net measures of the effects from explicit behavioral procedures (cf. Borkovec, 1972;Davison, 1968;Marcia et al, 1969;McGlynn et al, t971;Paul, 1966). While Borkovec et al quite satisfactorily showed a subset of their measures of shyness to be unresponsive to simple, preassessment, experimental-demand instructions, they did not show these measures of shyness to be unresponsive to any of the elaborate, multisession placebo treatments that fear-therapy researchers might actually employ.…”
mentioning
confidence: 89%
“…The procedure labeled "pseudotherapy" was a version of the relaxationplus-irrelevant-imagery placebo strategy that was popularized by Davison (1968) and used widely by behavioral investigators up to a few years ago. It is treated as a placebo here because it has not heretofore been shown to have demonstrable therapeutic impact and because it is not active theoretically.…”
Section: "Treatm En T"mentioning
confidence: 99%
“…En ce qui concerne les traitements portant sur l'anxiété sociale et les phobies, il semble que l'exposition à l'agent anxiogène constitue l'ingrédient principal responsable de la baisse d'anxiété (Lamontagne, 1973;Marks, 1978). Ainsi, un certain nombre d'études ont démontré qu'un traitement de désensibili-sation systématique, où le sujet se voit confronté à la situation anxiogène, pouvait entraîner une baisse du niveau d'anxiété (Davison, 1968;Garlington et Coder, 1968;Goldfried, 1971;Kanter et Goldfreid, 1979;Meichenbaum, Gilmore et Fedoravicius, 1971). Certains programmes de formation universitaire d'enseignants, comme c'est le cas pour la présente étude, sont structurés de façon à exposer graduellement et systématiquement les étudiants à des situations d'enseignement (laboratoires d'enseignement) entre pairs.…”
unclassified
“…von der psychoprophylaktischen Vorbe reitungsmethode nach Leboyer [1974] -auch Verhaltenstherapeuten auf den Plan gerufen. Die Desensibilisierungstechnik [Wengle, 1974;Paul, 1966] gilt als bislang effektivste Möglichkeit zur Reduktion relativ um schriebener Ängste [Meyer und Chesser, 1971;Paul, 1968;Davison, 1968]. Diese Methode schliesst eine Reihe von Massnahmen ein, die darauf abzie len, «in der Therapiesituation Bedingungen herzustellen, unter denen der Patient mit bestimmten, für ihn angstauslösendcn Situationen oder Stimuli konfrontiert werden kann, ohne dass bei ihm nennenswerte Angstreaktio nen auftreten [Wengle.…”
unclassified